The Dynamics of the Electoral Geography of the Five Star Movement: The Role of Territorial Area and Municipality Size. Issue 5 (20th October 2019) - Biancalana, Cecilia; Colloca, Pasquale
ABSTRACT: The aim of the article is to trace the evolution of the Movimento 5 Stelle (Five Star Movement [M.5.S.]) over the last four national elections (the 2013 and 2018 general elections and the 2014 and 2019 European elections). In particular, our goal is to understand how the electoral support for the party changed, in the context of the broad transformations of the Italian electoral geography. In order to accomplish this goal, we investigate the explanatory role of the spatial dimension on electoral support, specifically in terms of geographical zone and municipality size. The M.5.S. is also compared with the two parties that reported the best results in the last European elections: the Lega (League) and the Partito Democratico (Democratic Party [P.D.]). Our results show that the recent European elections do not represent a turning point in the (electoral and geographical) history of the M.5.S.: its territorial rooting in the south of the country and in medium-sized municipalities are present from the 2014 European elections onwards. Interpretations and implications of these findings are discussed in the conclusions.